Study on Preparation of Bio-fertilizer with the Help of Microorganism for Insects Free Agriculture - Sharma, Harsha; Sharma, Kalpana (Current Topics in Agricultural Sciences Vol. 2, 2021)
Biological control is a natural ecological phenomenon. Which can be successfully used in the management of pesticides, and it can be a balanced, sustainable and economical pest control tool. The use of micro-organisms for pesticides is called microbial control. This is a new aspect of biological control, in which the use of pesticides microbes is used for their control. By practically looking for microbial control of insects and looking after the natural enemies of pests, their number can be increased by utilizing them for control of pesticides, which is available by marking experts and accessible. Inter-essentially, we can resolve this solution in such a way. It is necessary to determine the timing of the use of micro-organisms carefully on the weakening of the life cycle of the harmful insect. Their individual age, i.e. life cycle, is reduced due to their use, be sure to note the pre-production method. We can naturally take control of microorganisms; we also have to use the microscope in this work in a variety of tests. This study highlights the potential that some microorganisms have in improving the conservation status of plants classified as vulnerable, endangered and even critically endangered.